Effectiveness of Gratitude Therapy in Diabetes Management: A Qualitative Study - Safeya Makhmur; Sangeeta Rath (Health Psychology Research)
The present study involves a Qualitative research design. The study intends to assess the effectiveness of interventions on the diabetic participants. In the present study, four participants screened with high perceived stress, moderate depression, poor sense of gratitude, were selected. The study consisted of three successive phases such as baseline assessment, intervention, and follow-up. Pre-test and Post-test design were adopted. Qualitative data were expressed as percentages, and Schwartz and Blanchard’s technique was administered. Participants have shown improvement in positive dimension scores and there is reduction in negative dimension scores. Blood glucose level readings are also marked before, during, and after the intervention. Participants are found to control their blood glucose level, but the change in the glucose level is not clinically significant.